Impact of the Zero Maternal Death by Hemorrhage Strategy on health professionals’ self-perceived knowledge in managing postpartum hemorrhage - Gilson Geraldo de Oliveira; Mariana Larissa Oliveira dos Santos; Gabriel Costa Osanan; George Dantas de Azevedo; Reginaldo Antônio de Oliveira Freitas Júnior (Revista Brasileira de Ginecologia e Obstetrícia)
Abstract Objective: This study aimed to evaluate the results of the Obstetric Hemorrhage Prevention and Management Course – Zero Maternal Death by Hemorrhage Strategy (0MMxH) among healthcare professionals before and after participation. Methods: A quasi-experimental design was employed, assessing the educational intervention in a convenience sample of healthcare professionals who had participated in the 0MMxH at least one year prior. Participants completed a retrospective pre-post questionnaire sent via email, focusing on self-perceived knowledge levels and the adoption of best practices in postpartum hemorrhage (PPH) management. Results: Out of 129 professionals who completed the 0MMxH training, 85 (65.9%) responded to the questionnaire. The percentages of respondents reporting no or low knowledge before and after the course were: shock index (52.8% to 0%, before and after, respectively), blood loss estimation (35.2% to 1.1%), care sequence for PPH (44.6% to 0%), rational use of crystalloids (37.5% to 1.1%), non-pneumatic anti-shock garment (83.5% to 3.4%), and damage control surgery (74.1% to 8.1%). These results indicate a significant improvement in self-perceived knowledge. After the course, the highest adoption rates of best practices were for shock index (83.5%), blood loss estimation (67.1%), and use of warm crystalloids (58.8%). However, gaps remained regarding non-pharmacological interventions for PPH management. Conclusion: Participants reported improved knowledge on most topics covered by the 0MMxH. The program was recognized as a crucial factor in adopting effective PPH management practices, underscoring the importance of training in enhancing obstetric care.